Mulheres de fases: um ensaio etnográfico sobre quatro trajetórias de consumo de bens e serviços ligados à estética corporal - Lyrio, Isadora Rocha (2020)
ABSTRACT Abstract: This research aims to understand the aesthetic consumption from the trajectory of four women of different age groups. In this sense, my subjects are these women and their life narratives involving the consumption of goods and services r